Petrological and geochemical evidence for a hot crystallization path and a recharge filtering bypass at Antimilos, Milos volcanic field, Greece - Stamatios Xydous; Ioannis P. Baziotis; Stephan Klemme; Michael Bizimis; Pieter Z. Vroon; Jasper Berndt; James M. D. Day; Paul D. Asimow (Contributions to Mineralogy and Petrology, 2023)
Antimilos volcano in the South Aegean Volcanic Arc, Greece, comprises an andesite–dacite suite that follows a distinct evolutionary path than the main edifice of the Milos volcanic field, despite their proximity. Petrographic and geochemical analyses reveal that basaltic andesite to low-Si dacite lavas have similar phenocryst assemblages that indicate crystallization from hot, relatively dry magmas in an upper crustal storage region. Rare antecrystic high-Mg# clinopyroxene cores with low Y, low Dy, and high Sr contents record the cryptic involvement of amphibole, a phase nominally absent from the erupted products, in the deeper parts of the plumbing system. Low temperature antecrysts with textures recording various degrees of disequilibrium suggest a protracted history of interaction between the upper crustal reservoir and deeper mafic melts, forming mobile hybrid magmas that consequently erupt as highly mingled, crystal-rich lava domes. Antimilos magmas seem to have escaped recharge filtering in the upper crust and prolonged stalling, which is the process that is probably responsible for the paucity of mafic eruptions in the rest of the Milos volcanic system. Large extensional structures offshore of Antimilos promote rapid ascent of mafic melts, inhibiting prolonged stalling and interaction with the arc crust. This model highlights the dominant role of the regional stress field in generating petrologically distinct suites in the marginal parts of some volcanic fields.